2021
DOI: 10.1024/2673-8627/a000010
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Status of Healthcare Workers During the COVID-19 Outbreak

Abstract: Abstract. Background: The COVID-19 pandemic is a massive health crisis that has exerted enormous physical and psychological pressure. Mental healthcare for healthcare workers (HCWs) should receive serious consideration. This study served to determine the mental-health outcomes of 1,556 HCWs from 45 countries who participated in the COVID-19 IMPACT project, and to examine the predictors of the outcomes during the first pandemic wave. Methods: Outcomes assessed were self-reported perceived stress, depression sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 108 publications
0
14
0
Order By: Relevance
“…It is also a transitional period for younger students and carries the extra burden of adjusting from high school to university. Social support is important and predicts well-being in general and during the pandemic (Gloster et al, 2020; Nicolaou et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It is also a transitional period for younger students and carries the extra burden of adjusting from high school to university. Social support is important and predicts well-being in general and during the pandemic (Gloster et al, 2020; Nicolaou et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…6 Stress, insomnia, and COVID-19 fears were also common. Half of the HCWs showed moderate levels of perceived stress in one study 5 and 42% reported insomnia in a systematic review. 4 Finally, almost 42% of HCWs reported feeling fearful about COVID-19 and had anxiety related to becoming infected themselves and/or infecting a loved one.…”
Section: Introductionmentioning
confidence: 98%
“…Several solutions have been offered to contain the level of perceived stress among health workers, such as implementing measures to improve social support (Aydın et al. , 2021; Nicolaou et al. , 2021); introducing stress management programmes (Conti et al.…”
Section: Introductionmentioning
confidence: 99%
“…1. Introduction Among the negative consequences of the spread of highly contagious diseases, one of the most serious concerns examined in the literature is the damage to the mental health of the disease's affected population (Brooks et al, 2020;Cabarkapa et al, 2020;Chong et al, 2021;Chou et al, 2020;Dias Neto et al, 2021;Gloster et al, 2020;Huang and Zhao, 2020;Ji et al, 2017;Kamara et al, 2017;Tian et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation